BAX inhibitor‐1 regulates autophagy by controlling the IRE1α branch of the unfolded protein response. (1st June 2017) - Castillo, Karen; Rojas‐Rivera, Diego; Lisbona, Fernanda; Caballero, Benjamín; Nassif, Melissa; Court, Felipe A; Schuck, Sebastian; Ibar, Consuelo; Walter, Peter; Sierralta, Jimena; Glavic, Alvaro; Hetz, Claudio
Abstract :